Е. Р. фон Штерн у вітчизняній історіографії - Кузміщев, О.Г. (Археологія, 2013)
Подано праці вітчизняних дослідників, присвячені діяльності історика й археолога кінця XIX — початку XX ст. Е.Р. фон Штерна. Анализ отечественной историографии, посвященной историку и археологу конца XIX — начала XX в. Эрнсту Романовичу фон Штерну, показывает, что она развивалась согласно политической обстановке в СССР. Впервые итоги деятельности ученого были освещены еще при его жизни. Но из-за национальной принадлежности фон Штерна, его отъезда в Германию (1911 г.) и дальнейшие политические статьи о событиях в России его имя исчезло со страниц научных публикаций. И только после смерти ученого (1924 г.) появилась возможность напомнить о нем в мемориальных статьях и отметить его заслуги в различных областях исторической науки. После длительного замалчивания имени Э.Р. Штерна единичные упоминания о нем появляются в 50-х гг. и особенно 60-х. В частности, детальный анализ концепции Э.Р. Штерна греческой колонизации Северного Причерноморья осуществил В.В. Лапин в монографии 1966 г. Но истинный интерес к деятельности и личности фон Штерна начался с 90-х гг. Тогда появилось значительное число публикаций, в которых освещены и отдельные аспекты научной деятельности ученого (археологический, педагогический, эпиграфический, научноорганизационный), и в целом, и его биография. Но представляется, что ученый уровня фон Штерна заслуживает всестороннего и целостного монографического исследования. Analysis of homeland historiography dedicated to Ernst Romanovych von Stern, a historian and archaeologist of the end of the 19th – the beginning of the 20th c., shows that it developed according to the political situation in the USSR. For the first time, the results of the scholar’s activity were elucidated during his life yet. However, because of von Stern’s nationality, his departure to Germany (1911), and his further articles on the events in Russia, his name vanished from the pages of scientific publications. And only after he died in 1924 it became possible to remind about him in memorial papers and to record his achievements in various fields of historic science. After E.R. Stern’s name was concealed for a long time, separate mentions about him appeared in the 1950-s and especially in the 1960-s. In particular, V.V. Lapin in his monography in 1966 conducted the further analysis of E.R. Stern’s conception of Greek colonization at the north coast of the Black Sea. However, the true interest to von Stern’s activity and personality started since the 1990-s. Significant number of publications appeared where both separate aspects of the scholar’s scientific activity (archaeological, pedagogical, epigraphic, and science organizational), as a whole, and his biography were elucidated. However, it is clear that the scholar of von Stern’s level deserves an integral comprehensive monographic research.